PERLINDUNGAN KONSUMEN TERHADAP BARANG RUSAK SAAT PENGIRIMAN EKSPEDISI EXPRESS - candra daniswara; Anak Agung Istri Ari Atu Dewi (Kertha Negara : Journal Ilmu Hukum, 2023)
The direction of this research is to understand what causes damage to goods in transit and how consumer protection law validates sender liability for shipping services. This study uses prescriptive rules research with a rules approach. As a result of our research, we found this shipping service to be very useful as it allows us to deliver the goods we want in an easy and practical manner. A freight forwarding service is a form of public service that facilitates the safe delivery of goods from one place to another and can be billed for that service. Delivery of objects can take the form of written data, logistics, electronic products, etc. Unfortunately, many consumers also suffer losses during the delivery of their goods, so more must be done to protect consumers and respect their rights. The carrier will be responsible for the goods damaged in transit and compensate for the damage caused by the owner of the goods. We need laws to protect the people involved, especially consumers. Provisions for consumer legal protection against damage to goods during shipping are contained in the Consumer Protection Act No. 8 of 1999.